2016
DOI: 10.1016/j.envpol.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Maximum Entropy space/time estimation of surface water chloride in Maryland using river distances

Abstract: Widespread contamination of surface water chloride is an emerging environmental concern. Consequently accurate and cost-effective methods are needed to estimate chloride along all river miles of potentially contaminated watersheds. Here we introduce a Bayesian Maximum Entropy (BME) space/time geostatistical estimation framework that uses river distances, and we compare it with Euclidean BME to estimate surface water chloride from 2005 to 2014 in the Gunpowder-Patapsco, Severn, and Patuxent subbasins in Marylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This study showed the role of shoot fresh weight as the key determinant of improved performance under salinity as it correlated well with all other growth variables (Table 6). Geostatistical methods, which have a wide range of applications in water quality (Jat and Serre 2016) and exposure assessment (Li et al 2010) can also be used for soil salinity through pH estimation and accordingly, tolerant bean varieties can be planted for better crop production and harvest. This study can be helpful for improving the choice of genotype suited to perform best under known conditions of salinity.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed the role of shoot fresh weight as the key determinant of improved performance under salinity as it correlated well with all other growth variables (Table 6). Geostatistical methods, which have a wide range of applications in water quality (Jat and Serre 2016) and exposure assessment (Li et al 2010) can also be used for soil salinity through pH estimation and accordingly, tolerant bean varieties can be planted for better crop production and harvest. This study can be helpful for improving the choice of genotype suited to perform best under known conditions of salinity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to that, ease of data collection, flexible control of spatial and temporal resolution, low operational costs, and safer work environment underpins the possibility of having a "UAV as a service" data collection market in the foreseeable future. The underlying technological advancement in multi-scale visual mapping, 3D digital modeling and time series analysis using SfM algorithms also empowers research in sectors outside forestry such as construction management [105], water contamination [106], archaeology [107], energy systems [108], computational biology [109] and habitat conservation [110]. Nevertheless, there are a lot of challenges associated with regulated, safe, and comprehensive applications of UAV remote sensing [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ground classification routines can be broadly categorized into surface-based, morphology-based and slope-based [53]. Surface-based algorithms can be further subdivided into progressive triangulated irregular network densification (PTD) and interpolation-based algorithms [54][55][56]. We tested three published, academically licensed or open-source ground-point selection methods, all designed for ALS data.…”
Section: Uas Dap Ground-point Classificationmentioning
confidence: 99%